The Role Of Quantum Healing In Psychological Wellbeing - Isnaeni, Herliyana (Pelopor Publikasi Akademika, 2025)
Psychological well-being is a crucial aspect that is closely related to physical and mental health and how individuals function optimally in their lives. This research aims to determine the role of quantum healing as a holistic approach that integrates mind-body-spirit alignment practices in improving psychological well-being. Using qualitative research methods with a systematic literature review. There are references to 10 journal articles with a publication range from 2020 – 2024 which explore the principles of quantum healing, its application and effectiveness in psychological well-being. The analysis results show that the quantum healing principle can reduce muscle and nerve tension, reduce stress and anxiety, reduce the perception of pain, increase inner peace, increase feelings of relaxation and happiness, improve sleep quality and improve quality of life. This indicates that quantum healing as an alternative therapy plays a positive role in psychological well-being.